MENELUSURI METODOLOGI TAFSIR AL-HIJRI - Ruslan Sangadji (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
AbstractSystematics Tafsir Al-Hijri was the beginning of the introduction and then the table of contents, and then enter the discussion of the text. Each verse is classified and given a theme. There are 44 themes that became staples of the discussion and any description of the themes discussed with language that is very straightforward. Method of preparation of Tafsir Al-Selusuh order models. From one paragraph to the next verse in surah al-Maidah outlined, with the earlier grouping some of the verse to one specific theme. Thus, Tafseer tahlili belonged. But because it also arranged upon themes that exist, it also has implemented a systematic model of thematic.  systematic presentation of the thematic series is a form of writing that the interpretation of the structure of his speech refer to on specific themes or on a particular paragraph. The pattern of interpretation belongs to adabi-ijtimaiy. The meaning is dominant in his Tafseer connects with the reality of social and societal.Keywords: methodology, the interpretation of Al- Hijri.